Ecological coefficient of performance analysis and optimization of an irreversible regenerative-Brayton heat engine - Ust, Y; Sahin, B; Kodal, A; Akcay, IH (ELSEVIER SCI LTD, 2006)
In this paper. a performance optimization based on the ecological coefficient of performance (ECOP) criterion has been carried Out for an irreversible regenerative Brayton heat-engine. The results obtained were compared with those using the power-output criterion and alternative ecological performance objective-function defined in the literature. The design parameters. under the optimal conditions. have been derived analytically and their effects on the engine's performance have been discussed. It is shown that, for the regenerative Brayton-engine, a design based on the maximum ECOP conditions is more advantageous from the point-of-view of entropy generation rate, thermal efficiency and investment cost. (C) 2005 Elsevier Ltd. All rights reserved.
Keywords: Brayton heat engine; regenerative; irreversible; ecological optimization; MAXIMUM POWER-DENSITY; ENTROPY GENERATION MINIMIZATION; CYCLE; EFFICIENCY; THERMODYNAMICS; CRITERION; Energy & Fuels; Engineering